CHARACTERISTICS OF STUDENTS' SELF-CONTROL AS COMPONENT OF EDUCATIONAL ACTIVITY (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the characteristic of the self-control ofpupils as a component of their instructional and cognitive activity, there are represented the kinds and the structural links of instructional self-control.